Allogeneic stem cell transplantation for rheumatic autoimmune diseases - Hügle, Thomas (Medicine Reports Ltd, 2010)
Haematopoietic stem cell transplantation (HSCT) has evolved from an experimental concept to an effective treatment option for severe autoimmune diseases and has a unique ability to restore immune regulation. It is a complex multistep procedure involving the administration of high doses of immunosuppressive medication and transplantation of stem cells. Most HSCT procedures in autoimmune disease have involved autologous stem cells. In the case of allogeneic transplantation, stem cells are derived from peripheral blood or bone marrow of a healthy HLA-matched donor. Allogeneic HSCT has curative potential based on studies in experimental models of autoimmune disease, case reports, and a registry analysis but carries significant risks of rejection and graft-versus-host disease. Unless these risks become manageable, allogeneic HSCT should be offered only if all alternative treatment options have failed, if a patient has a suitable donor, and if a patient still has a chance to benefit significantly from the procedure.